The Perilous Journey from Melancholy to Love: A Kristevan Reading of Le Médianoche amoureux - Karen D. Levy (Studies in 20th & 21st Century Literature, 1995)
Since the publication of Michel Tournier's first novel Vendredi ou les limbes du Pacifique in 1967, in which his protagonist Robinson makes fruitful the very earth of his desert island and eventually accedes to the cosmic transcendence embodied in his mentor and companion Vendredi, this contemporary French writer has boldly explored alternative forms of sexual expression that challenge traditional biological definitions of identity as well as norms of accepted behavior. The basis of his investigations is the anguish-ridden separation from the maternal, as experienced under diverse manifestations usually by male characters, and the irremediable solitude which then stretches over that empty space. In this study, we shall explore Tournier's latest and perhaps most unexpected treatment of the phenomenon of separation and loss as depicted in his latest anthology of short stories Le Médianoche amoureux from the point of view of two of Julia Kristeva's most recent theoretical analyses. Her works probe precisely the kind of psychological wounds from which Tournier's protagonists suffer and, as we shall see, suggest possibilities for healing that significantly enhance our understanding of his undertaking. Kristeva's discussion of melancholy in Soleil noir; Dépression et mélancolie and her demystifying analysis of the intricacies of amatory discourse in Histoires d'amour will enable us to discern the kind of movement that draws the disparate stories of Le Médianoche amoureux together and will reveal how this latest of Tournier's works greatly extends the scope of his preoccupations without closing any of the other doors he has so daringly opened.
Keywords: Michel Tournier; Vendredi ou les limbes du Pacifique; Robinson; fruitful; earth; desert island; cosmic transcendence; mentor; Vendredi; contemporary; French; sexual expression; alternative; identity; challenge; norms; behavior; maternal; separation; male characters; male; solitude; space; loss; Le Médianoche amoureux; anthology; short stories; Julia Kristeva; psychological wounds; & quot; Soleil noir; Dépression et mélancolie& quot; analysis; Histoires d& #x27; amour